Film, Lacan and the subject of religion a psychoanalytic approach to religious film analysis - Nolan, Steve (London ; New York : Continuum, 2009)
In their study of religion and film, religious film analysts have tended to privilege religion. Uniquely, this study treats the two disciplines as genuine equals, by regarding both liturgy and film as representational media. Steve Nolan argues that, in each case, subjects identify with a represented 'other' which joins them into a narrative where they become participants in an ideological 'reality'. Finding many current approaches to religious film analysis lacking, Film, Lacan and the Subject of Religion explores the film theory other writers ignore, particularly that mix of psychoanalysis, M
List of Abbreviations; Introduction; An Overview; With Thanks; Part One: Current Approaches to Religious Film Analysis; Introduction to Part One; 1 Phenomenological Interpretations: Film as Sacrament; 2 Literary Interpretations: Film as Visual Story; 3 Anthropological Interpretations: Film as Religion; Part Two: Representation in Liturgy and Film; Introduction to Part Two; 4 Liturgical Representation: 'Others', Narratives and Ideological 'Realities'; 5 Cinematic Representation: 'Others', Narratives and Ideological 'realities'; Part Three: What Can Film Theory Offer Liturgy?
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Motion pictures -- Religious aspects; Motion pictures -- Psychological aspects; Motion pictures -- Moral and ethical aspects; Religion in motion pictures; Lacan, Jacques, -- 1901-1981.; RELIGION -- Christianity -- General; RELIGION -- Ethics; Electronic books